YOUTH SLANG AS A REFLECTION OF SOCIAL IDENTITY IN TEENAGE COMMUNITIES - Bahar, Aulia Aldilah; Fauzi, Unzila Alzura; Al Anwar, Sylvia Febbryani; Istama, Nanda Rizka; Maulana, Aditia Hendri; Nargis, Nargis (VARIABLE RESEARCH JOURNAL, 2025)
This study aims to identify the types of slang used by teenagers and explain the reasons behind their use in the context of social identity. Slang is defined as an informal language used by certain social groups for internal communication, reflecting the values and experiences of its users. This research uses a descriptive qualitative method with data collection techniques through semi-structured interviews and observations on social media, especially among high school students aged 15-17 years. The results show that there are 10 slang terms that are often used by teenagers, such as “BFR”, “tea”, “C U”, “PAP”, “YOLO”, “salty”, “Kk”, “Btw”, “fix” “YOLO”, and “ASAP”. This study also found that the use of slang can strengthen teenage social identity as well as influence intergenerational communication patterns, where adults often do not understand or negatively judge teenage use of slang. Thus, this study provides insights into how informal language plays a role in shaping social identity and interaction dynamics in teenage communities.